2021
DOI: 10.1002/suco.202100170
|View full text |Cite
|
Sign up to set email alerts
|

Coupled thermo‐hydro‐mechanical analysis of reinforced concrete beams under the effect of frost damage and sustained load

Abstract: Frost damage is an important deterioration parameter for reinforced concrete (RC) structures in cold and humid environment, which usually acts simultaneously with sustained load caused by self-weight, immobile weight, and so forth. This article conducts a thermo-hydro-mechanical simulation on the structural behavior of RC beams under the coupled effect of frost damage and sustained load. This simulation approach starts from the microscale materialbased frost damage model of multicomponent substance to the macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Different damaged zones (compression or tension) with various damage depths were prepared and investigated (Fig. 11) [26,27]. After validation with experimental evidence, a parametric study regarding the impact of reinforcement type was conducted.…”
Section: Frost Damage and Static Loadmentioning
confidence: 99%
“…Different damaged zones (compression or tension) with various damage depths were prepared and investigated (Fig. 11) [26,27]. After validation with experimental evidence, a parametric study regarding the impact of reinforcement type was conducted.…”
Section: Frost Damage and Static Loadmentioning
confidence: 99%
“…Ultimately, an evaluation equation was proposed for instant strength evaluation. The recent articles [13,14] revealed that the member performance was degraded by the environmental impact, proving the necessity of long-term monitoring to secure the safety of structures.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforced concrete structures are one of the most widely used forms of building structures, but most structures suffer from environmental corrosion [1-3], natural hazards (floor and wind loads, fires, earthquakes, etc.) [3][4][5][6][7], impacts [8,9], and increasing vehicle loads [6,10]. The structural damage caused by extreme loads has already caught the attention of scholars, driving the development of structural health monitoring (SHM), which is assisted by sensors and advanced algorithms [7,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7], impacts [8,9], and increasing vehicle loads [6,10]. The structural damage caused by extreme loads has already caught the attention of scholars, driving the development of structural health monitoring (SHM), which is assisted by sensors and advanced algorithms [7,[11][12][13]. In order to determine structural behavior under failure and to provide sufficient data for the SHM, destructive tests on structures, especially bridges, are essential.…”
Section: Introductionmentioning
confidence: 99%